Shear Bond Strength of Orthodontic Brackets after Accelerated Artificial Aging - Drubi-Filho, Brahim; Sousa, Ana Beatriz Silva; Chinelatti, Michelle Alexandra; Panzeri Pires-de-Souza, Fernanda Carvalho (The Journal of Dentists, 2013)
The purpose of this study was to compare the shear bond strength (SBS) and the adhesive remnant index (ARI) after Accelerated Artificial Aging (AAA) of metal orthodontic brackets bonded with self-polymerizing (Concise Ortodôntico - CS, 3M Unitek) and light activated (Transbond Plus Color Change - TPCC, 3M Unitek) composites to enamel after different surface treatments. Methodology: 60 human premolars were separated into 5 groups (n=12): Group I - 37% phosphoric acid (PA Dental Gel, Dentsply) and CS; Group II – PA + Primer and CS; Group III - PA and TPCC; Group IV - PA + XT Primer (3M Unitek) and TPCC; and Group V – Transbond Plus Self Etching Primer - SEP (3M Unitek) and TPCC. Twenty-four hours after bracket bonding, half of the specimens from each group were submitted to AAA for 960 hours. The samples were submitted to the shear bond strength (SBS) test in a universal test machine (0.5mm/min). ARI was evaluated under a loupe (10X) and quantified using a score (0-3). Data were submitted to 2-way ANOVA and Bonferroni’s test (????a=5%). Results: Group II without AAA showed the highest mean value of SBS (p<0.05) in comparison with Groups III and V, which showed the lowest mean of SBS, when comparing the adhesive systems used. All groups without AAA presented a greater frequency of score 3, regarding the ARI. There was an increase in the frequency of scores 1 and 2 when specimens were submitted to AAA, Conclusion: AAA did not influence the SBS of brackets, but reduced the area of ARI.